2016
DOI: 10.1590/s1677-5538.ibju.2014.0485
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted radical prostatectomy learning curve for experienced laparoscopic surgeons: does it really exist?

Abstract: Background Robotic-assisted radical prostatectomy (RALP) is a minimally invasive procedure that could have a reduced learning curve for unfamiliar laparoscopic surgeon. However, there are no consensuses regarding the impact of previous laparoscopic experience on the learning curve of RALP. We report on a functional and perioperative outcome comparison between our initial 60 cases of RALP and last 60 cases of laparoscopic radical prostatectomy (LRP), performed by three experienced laparoscopic surgeons with a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…Machado and colleagues [ 14 ] reported that surgeons with more than 200 LRP cases obtained similar oncological results in the first 60 cases using RARP. They found mean operating time of 236 minutes and blood loss of 245.6 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Machado and colleagues [ 14 ] reported that surgeons with more than 200 LRP cases obtained similar oncological results in the first 60 cases using RARP. They found mean operating time of 236 minutes and blood loss of 245.6 ml.…”
Section: Discussionmentioning
confidence: 99%
“…In another quite similar study, the first 60 RRP and the last 60 LRP results of 3 surgeons with over 200 LRP experience were compared and it was reported that surgery time, blood loss volume and surgical margin positivity were significantly higher in patients who underwent robotic prostatectomy (153 mins-236 mins, 202 ml-244 ml and 12.5-31.6%, respectively). However, potency and continence rates were similar with each other or in favor of robotic surgery (16). On the other hand, in another study in which first 50 robot-assisted laparoscopic prostatectomy (ARP) and first 50 open radical retropubic prostatectomy (ORRP) results of a surgeon without previous laparoscopy experience was evaluated, operative time and blood loss volume were found to be lower in ARP than in ORRP, meanwhile complication, surgical margin positivity, continence and potency rates were found to be similar.…”
Section: Introductionmentioning
confidence: 57%
“…In the first reported series in Brazil, Colombo Jr et al reported mean estimated bleeding of 480mL (100-1800) and transfusion necessary in two patients (2%). One study from Tobias-Machado and another from Lott found mean blood loss of 245.6mL and 212mL respectively ( 21 , 22 ). In our series, mean EBL was 95mL (±158), no patients had blood transfusions during surgery, but two (3.3%) required it during postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from initial series in some high volume centers showed median surgical duration from 215 to 274 minutes ( 24 , 25 ). Series from our country reported mean or median surgical times from 175 to 298 minutes ( 3 , 21 , 22 , 26 ). In 2005 Patel et al described an extremely short mean operative time of 141 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation